A compact and flexible induction furnace for in situ X‐ray microradiograhy and computed microtomography at Elettra: design, characterization and first tests. (12th June 2018) - Kudrna Prašek, Marko; Pistone, Mattia; Baker, Don R.; Sodini, Nicola; Marinoni, Nicoletta; Lanzafame, Gabriele; Mancini, Lucia
Abstract : An induction furnace for in situ high‐resolution synchrotron and laboratory hard X‐ray microradiography and computed microtomography developed at the Elettra synchrotron radiation facility is described. Abstract : A compact and versatile induction furnace for in situ high‐resolution synchrotron and laboratory hard X‐ray microradiography and computed microtomography is described. The furnace can operate from 773 to 1723 K. Its programmable controller enables the user to specify multiple heating and cooling ramp rates as well as variable dwell times at fixed temperatures allowing precise control of heating and cooling rates to within 5 K. The instrument can work under a controlled atmosphere. Thanks to the circular geometry of the induction coils, the heat is homogeneously distributed in the internal volume of the graphite cell ( ca . 150 mm 3 ) where the sample holder is located. The thermal gradient within the furnace is less than 5 K over a height of ca . 5 mm. This new furnace design is well suited to the study of melting and solidification processes in geomaterials, ceramics and several metallic alloys, allowing fast heating (tested up to 6.5 K s −1 ) and quenching (up to 21 K s −1 ) in order to freeze the sample microstructure and chemistry under high‐temperature conditions. The sample can be held at high temperatures for several hours, which is essential to follow phenomena with relatively slow dynamics, such as crystallization processes in geomaterials. The utility of the furnace is demonstrated through a few examples of experimental applications performed at the Elettra synchrotron laboratory (Trieste, Italy).